Bispectral index in dogs at three intravenous infusion rates of propofol - Lopes, Patricia C. Ferro; Nunes, Newton [UNESP]; Paula, Danielli P.; Nishimori, Celina T. D.; Guerrero, Piedad N. H.; Conceicao, Elaine D. V. (Blackwell Publishing, 2008)
Objective To establish the correlation between the bispectral index (BIS) and different rates of infusion of propofol in dogs.Study design Prospective experimental trial.Animals Eight adult dogs weighing 6-20 kg.Methods Eight animals underwent three treatments at intervals of 20 days. Propofol was used for induction of anesthesia (10 mg kg(-1) IV), followed by a continuous rate infusion (CRI) at 0.2 mg kg(-1) minute(-1) (P2), 0.4 mg kg(-1) minute(-1) (P4) or 0.8 mg kg(-1) minute(-1) (P8) for 55 minutes. The BIS values were measured at 10, 20, 30, 40, and 50 minutes (T10, T20, T30, T40, and T50, respectively) after the CRI of propofol was started. Numeric data were submitted to analysis of variance followed by Tukey test (p < 0.05).Results The BIS differed significantly among groups at T40, when P8 was lower than P2 and P4. At T50, P8 was lower than P2. The electromyographic activity (EMG) in P2 and P4 was higher than P8 at T40 and T50.Conclusion An increase in propofol infusion rates decreases the BIS values and EMG.
Keywords: bispectral index; intravenous anesthesia; monitoring; propofol